A smart energy monitoring system using ESP32 microcontroller - Hala Jarallah El-Khozondar; Shady Y. Mtair; Khaled O. Qoffa; Omer I. Qasem; Ahmad H. Munyarawi; Yasser F. Nassar; Ehab H.E. Bayoumi; Ahmed Abd El Baset Abd El Halim (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2024)
Gaza's electrical deficit has resulted in the rise of new energy suppliers that sell power from private generators at higher prices. Consumers have challenges because they cannot tell whether their energy originates from the utility or private generators, resulting in unexpectedly large bills owing to a lack of an electronic monitoring system. This study fills this gap by developing a low-cost IoT energy monitoring system that provides real-time information on energy use (hourly, daily, and monthly) to assist consumers in managing their usage and expenditures. An ESP32 microcontroller is used in the system to gather data from energy meters, analyze it, and deliver updates to users via WhatsApp over a secure Wi-Fi connection via the Blynk platform. Experimental findings show that the system accurately captures voltage, current, active power, and cumulative power consumption and transmits this information to customers in real time.